Do We Experience Misconceptions?: An Ontological Review of Misconceptions in Science - Nadi Suprapto (Indonesia Approach Education, 2020)
A misconception is a misunderstanding in connecting a concept with other concepts, between new concepts and old concepts that are already in the minds of students, so that the wrong concepts are formed. Students' conceptions are different or contrary to the conceptions of the scientists. There are five kinds of misconceptions, namely: (a) preconceived notions; (b) non-scientific beliefs; (c) conceptual misunderstandings; (d) misconceptions of local languages (vernacular misconceptions); and (e) factual misconceptions. The causes of misconceptions are four parts: students, teachers, teaching materials or literature, context and teaching methods. It is expected that by knowing the types and causes of students' misconceptions in understanding science, it will be easier for teachers to find solutions in teaching science concepts. Examples of data related to misconceptions in physics are illustrated to reinforce explanations.